Crescent on the Island of Gods, Traces of Islamic Village in Kusamba-Bali - Farninda Aditya (Al-Albab, 2016)
I Gde Parimartha, Ida Bagus Gde Putra, Luh Pt.Kusuma Ririen. 2012. Bulan Sabit di Pulau Dewata, Jejak Kampung Islam Kusamba-Bali. Yogyakarta: Religious and Cross-cultural Studies (CRCS) Graduate School, Gadjah Mada University YogyakartaBali, a beautiful island well known all over the world, fascinates many visitors from various countries and has a religious identity as its nickname reflects, the Island of the Gods. Although famous as a Hindu land, Bali has an Islamic Village, where Muslims can live side by side with Balinese Hindus. In view of the events of the Bali Bombing, in 2002 in Kuta and 2005 in Jimbaran, of course, there have been social and religious tensions between these two faiths. The tragedy has indeed left a change of attitude that is a strengthening of political identity of the Balinese-ness. This situation is presented in a book entitled, Bulan Sabit di Pulau Dewata, Jejak Kampung Islam Kusamba-Bali (Crescent on the Island of Gods, Traces of Islamic Village in Kusamba-Bali).